Beyond UFOs : the search for extraterrestrial life and its astonishing implications for our future - Bennett, Jeffrey O. (Princeton University Press, 2011)
Describes the startling discoveries being made in the very real science of astrobiology, an intriguing new field that blends astronomy, biology, and geology to explore the possibility of life on other planets. Jeffrey Bennett takes readers beyond UFOs to discuss some of the tantalizing questions astrobiologists grapple with every day: What is life and how does it begin? What makes a planet or moon habitable? Is there life on Mars or elsewhere in the solar system? How can life be recognized on distant worlds? Is it likely to be microbial, more biologically complex--or even intelligent? What would such a discovery mean for life here on Earth?--From publisher description.